Law Enforcement of Terrorism Crimes Associated with Foreign Terorist Fighter ISIS Cases - Qurrata A'yun (Universitas Syiah Kuala, 2021)
This study aims to discuss the position of terrorism in international criminal law and law enforcement against terrorism crimes committed by the Islamic State of Iraq and Syiriah (ISIS) Foreign Terrorist Fighter (FTF). The research method used in this research study is a normative juridical legal research method. In some literature, crimes of terrorism in international criminal law are categorized as extraordinary crimes because of their systematic, organized and widespread nature. Law enforcement against the FTF ISIS for crimes of terrorism can basically be carried out by means of preventive measures as preventive and repressive measures as penal measures which in this case can be prosecuted based on the legal rules of the perpetrator's country of origin and allowed to make arrests, prosecutions and punishments or attempts. Extradition if necessary. In addition, law enforcement based on international criminal law can also be pursued if the crimes of terrorism committed by the perpetrators cause things that have an impact on the international community and qualify as stipulated in the Rome Statute.